“I would like support from school when it comes to doing extra to get into one of the top universities" How do high achieving history students respond to University preparation classes? - Hemsley, L (2015)
High-attaining students from non-selective state schools still apply to Oxford or Cambridge University in fewer numbers than their independent or grammar school peers. Comprehensive schools have been tasked with doing more to encourage and support students to make applications, but with very little guidance on what form this support should take. To explore this issue, this project focuses specifically on History. An analysis of the characteristics that elite universities expect of their History applicants makes it clear that teaching to meet the requirements of A-level History alone would fall short of developing these traits. This project proposes a solution: extra-curricular University Preparation Classes for high-attaining History students. Adopting a qualitative approach to action research, I captured both student and teacher voice through questionnaires at key points of the programme, together with a teacher journal, student work and group interviews. The classes were found to have a positive impact on the development of the characteristics of high performance in History, as well as affecting the rationale of students' university intentions. This paper ends by calling for greater collaboration between teachers and for universities' Widening Participation programmes to focus further on subject teachers' capacity to implement change in schools as a means to address the applications gap.